2019
DOI: 10.1098/rstb.2018.0359
|View full text |Cite
|
Sign up to set email alerts
|

Do synaesthesia and mental imagery tap into similar cross-modal processes?

Abstract: Synaesthesia has previously been linked with imagery abilities, although an understanding of a causal role for mental imagery in broader synaesthetic experiences remains elusive. This can be partly attributed to our relatively poor understanding of imagery in sensory domains beyond vision. Investigations into the neural and behavioural underpinnings of mental imagery have nevertheless identified an important role for imagery in perception, particularly in mediating cross-modal interactions. However, the phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…It is thus not surprising that synaesthetes would have superior understanding of unfamiliar sound-symbolic foreign words, as found in Bankieris & Simner's [128] experiment, suggesting that sound symbolism relies on the type of cross-modal integration that characterizes synaesthesia to an exaggerated degree. Overall, the enhanced cross-modality in synaesthesia has been ascribed to the hyper-connectivity of a synaesthete's brain ([114,115,117,129]; more on this in §5).…”
Section: Cross-modality and Aggression: Two Dimensions Impaired In Disorders Implicating Problems With Languagementioning
confidence: 99%
“…It is thus not surprising that synaesthetes would have superior understanding of unfamiliar sound-symbolic foreign words, as found in Bankieris & Simner's [128] experiment, suggesting that sound symbolism relies on the type of cross-modal integration that characterizes synaesthesia to an exaggerated degree. Overall, the enhanced cross-modality in synaesthesia has been ascribed to the hyper-connectivity of a synaesthete's brain ([114,115,117,129]; more on this in §5).…”
Section: Cross-modality and Aggression: Two Dimensions Impaired In Disorders Implicating Problems With Languagementioning
confidence: 99%
“…A second experiment, involving 16 English-speaking grapheme-colour synaesthetes and 22 controls, found that induced colours in synaesthesia evoked cross-modal correspondences of weight, considered a tactile property of objects, in a manner that was consistent with that experienced for veridical colours (red/ blue perceived as heaviest and yellow as lightest). Thus, the authors provide further evidence of enhanced imagery as one of the hallmarks of synaesthesia and stress the importance of a cross-modal perspective on this topic [15].…”
Section: Mental Imagerymentioning
confidence: 66%
“…Indeed, two of the articles of this special issue are specifically concerned with what synaesthesia can tell us about imagery, and vice versa. O'Dowd et al [15] argue that understanding of these relationships has been limited by a lack of knowledge about the nature of imagery for royalsocietypublishing.org/journal/rstb Phil. Trans.…”
Section: Mental Imagerymentioning
confidence: 99%
See 1 more Smart Citation
“…Even more interestingly, sights of touching evoke activity in somatosensory cortex (Hansson et al, 2009), visual cues to an object's surface properties evoke activity in secondary somatosensory cortex (Sun, Welchman, Chang, & Luca, 2016), and the mere sight of photographs (Proverbio, D'Aniello, Adorni, & Zani, 2011), and lipreading (watching a speaker's lips during face-to-face conversation; Calvert et al, 1997) activate auditory cortex. These particular findings together suggest the role of crossmodal mental imagery, the formation of mental image in a sensory modality from the stimulation or experience in another sensory modality, in perception and neuroplasticity: what people imagine in their minds can affect how they perceive the world, and how the sensory cortex reorganizes in absence of actual stimulation (e.g., Berger & Ehrsson, 2018;Nanay, 2018;O'Dowd, Cooney, McGovern, & Newell, 2019;Schmidt & Blankenburg, 2019;Spence & Deroy, 2013;Wise, Frangos, & Komisaruk, 2016).…”
Section: Crossmodal Connectivity In Unisensory Perceptionmentioning
confidence: 99%